Attachment and family systems : conceptual, empirical, and therapeutic relatedness - Erdman, Phyllis, 1949-; Caffery, Tom (New York ; London : Routledge, 2003)
Attachment and Family Systems is a cogent and compelling text addressing the undeniable overlap between two systems of thought that deal with the nature of interpersonal relationships and how these impact functioning. In this enlightening work, leading thinkers in the field apply attachment theory within a systemic framework to a variety of life cycle transitional tasks and clinical issues.
Pt. 1. Theoretical overview -- Ch. 1. Implications of Attachment Research for the Field of Family Therapy / Robert S. Marvin -- Pt. 2. Family Perspective -- Ch. 2. Family-Level Emotional Climate and Its Impact on the Flexibility of Relationship Representations / Jean Talbot and James McHale -- Pt. 3. Life Cycle Transitions: Child and Adolescent Perspective -- Ch. 3. Attachment Theory Applied to Adolescents / Stacy Cretzmeyer -- Ch. 4. Adolescence and Attachment: From Theory to Treatment Implications / Susan K. Mackey -- Pt. 4. Life Cycle Transitions: Adult Perspective -- Ch. 5. Linking Work, Love, Individual, and Family Issues in Counseling: An Attachment Theory Perspective / M. Carole Pistole -- Ch. 6. The Systemic Nature of Couple Relationships: An Attachment Perspective / Judith A. Feeney -- Ch. 7. A Systemic Approach to Restructuring Adult Attachment: The EFT Model of Couples Therapy / Susan M. Johnson and Marlene Best -- Pt. 5. Specific Clinical Issues -- Ch. 8. Linking Systems and Attachment Theory: A Conceptual Framework for Marital Violence / Claire Worrell Haslam and Phyllis Erdman -- Ch. 9. An Approach to Treatment of Attachment Issues in the Adult and Child Subsystems Through the Use of Thematic Play Therapy in Conjunction with Couples Therapy / Michael R. Carns, Robin English, Leslie Huling, and Ann Cams -- Ch. 10. Integrative Systemic Approaches to Attachment-Related Trauma / Sylvia A. Marotta -- Ch. 11. Attachment Theory and Family Systems Theory as Frameworks for Understanding the Intergenerational Transmission of Family Violence / Pamela C. Alexander and Stephanie Warner.
Includes bibliographical references and index.
Keywords: Family psychotherapy; Attachment behavior